2018
DOI: 10.1111/eth.12822
|View full text |Cite
|
Sign up to set email alerts
|

Attendance to egg clutches by male Kurixalus eiffingeri increases hatching success and decreases predation by invasive slugs (Parmarion martensi) in Taiwan

Abstract: Invasive species have a significant impact on amphibians, and most notably Chytrid fungi together with a few vertebrates. However, invasive terrestrial invertebrates are seldomly demonstrated to have a negative effect on their host environment, and few studies investigated the behavioural interactions between invasive and local species, limiting our knowledge of the adaptive response adopted by local organisms. These responses include whether parenting animals recognize predators as threats to their offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For terrestrial‐breeding amphibians, laying eggs outside aquatic environments comes at a distinct cost, because their amniotic eggs are faced with a higher evaporation rate in terrestrial environments. High evaporation rates can lead to dehydration and egg stage mortality (Chuang et al., 2019; Kam, Hsu, et al., 1998). Since potential oviposition sites are not a limiting factor (Lin & Kam, 2008), it is logical that males would show a preference for sites that contain more water and give their offspring a better chance at survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For terrestrial‐breeding amphibians, laying eggs outside aquatic environments comes at a distinct cost, because their amniotic eggs are faced with a higher evaporation rate in terrestrial environments. High evaporation rates can lead to dehydration and egg stage mortality (Chuang et al., 2019; Kam, Hsu, et al., 1998). Since potential oviposition sites are not a limiting factor (Lin & Kam, 2008), it is logical that males would show a preference for sites that contain more water and give their offspring a better chance at survival.…”
Section: Discussionmentioning
confidence: 99%
“…Both males and females exhibit parental care in this species. Males care for their offspring by attending the eggs (Chen et al., 2007; Chuang et al., 2019; Kam et al., 1996), while females return periodically to feed their tadpoles by laying unfertilized eggs until tadpoles reach metamorphosis (Kam et al., 1996; Ueda, 1986). As other phytotelmata, the water levels of bamboo stump can fluctuate greatly depending upon the balance between evaporation and rainfall (Caldwell & de Oliveira, 1999; Lin & Kam, 2008; Wassersug et al., 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A higher stump and/or deeper stump depth also increases the di culties for predators to forage. As a result, the staying of egg-attending males would increase the egg survivorship (Chuang et al 2019). Secondly, the selection of deeper water by males may relate to the tadpole survival.…”
Section: The Adaptation Of Oviposition Site Selectionmentioning
confidence: 99%
“…Both males and females exhibit parental care, though the timing and type of care do not overlap between the sexes. Males care for their offspring by attending the eggs (Kam et al 1996;Chen et al 2007;Chuang et al 2019), while females return periodically to feed their tadpoles by laying unfertilized eggs until tadpoles reach metamorphosis (Ueda 1986;Kam et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The genus is found throughout south-central and south-eastern Asia, from as far west as northeast India, to as far south as Indonesia, as far east as the Ryuku Islands of Japan and north to the Himalayas and Taiwan ( Frost 2020 ). The genus is often associated with bamboo forests ( Chuang et al 2019 ; Nguyen et al 2020 ) although given the immense range of the genus, it is also present in several other habitat types ( Nguyen et al 2020 ). Outside of the Himalayas, in mainland China, its northernmost distribution is Chengdu, Sichuan at 30.36°N ( Hou et al 2021 ) and is also found in northern Taiwan at 25.3°N ( Wu et al 2016 ; Frost 2020 ).…”
Section: Introductionmentioning
confidence: 99%